Artisan minas cheese of Serro: proteolysis during ripening - Juliana de Oliveira Carneiro (Heliyon, 2020)
The Artisan Minas Cheese (AMC) is the oldest and most traditional Brazilian cheese, it is produced in several regions of the state of Minas Gerais, such as the Serro region. The most striking features of the AMC-Serro are the use of raw milk and natural bacteria from the whey, popularly known as pingo, as well as the use of the rind washing process. The aim of the present study was to evaluate the proteolysis of the AMC-Serro from three different producers, during 60 days of maturation, and to relate the proteolysis to the producing farms, the production season and the rind washing during ripening. For this purpose, TRICINE-SDS-PAGE, proteolysis extension and depth indices, moisture, and texture (firmness) were evaluated. It was concluded that the temperature and moisture of the cheeses, that were determined by the location of the ripening room, the production season and the rind washing, were the most important factors. The degree of proteolysis also had an impact on the water loss during ripening, with effect on cheese safety. The results obtained in this study may be used to better understand the transformations during ripening of AMC-Serro and help the small traditional farmers to improve their product's quality and stability.